Bilosomes as Soft Nanovesicular Carriers for Ropinirole Hydrochloride: Preparation and In- vitro Characterization - Samer Khalid Ali; Entidhar J. Al-Akkam (College of Pharmacy University of Baghdad, 2023)
Bilosomes are nanovesicular carriers that contain bile salts and non-ionic surfactants in a bilayer with cholesterol. These are more ultra-deformable, elastic, and flexible than other nanovesicular carrier. Ropinirole hydrochloride (RH) is a non-ergot dopamine D2-agonist. It is used to manage Parkinson's disease and to minimize "on-off" variations in levodopa responsiveness. The oral bioavailability is about 50% due to it being extensively metabolized in the liver, with an elimination half-life of about 6 h. The aim of this study was to enhance oral drug delivery and provide the sustained release of RH by preparing it as soft nanovesicular carriers (bilosomes). Eight formulas of RH bilosomes were prepared by a reverse-phase evaporation method using mixed surfactant (span®60: tween®60 at 1:2 ratio), cholesterol and sodium deoxycholate as bile salt. All formulas were evaluated for their drug content, entrapment efficiency, vesicle size, polydispersity index, zeta potential, drug release, transmission electron microscopy and fourier transform infrared spectroscopy. Results showed all prepared RH bilosomes were in nano-range with vesicle size ranging (from 124.40±10.60 to 294.60±11.50) nm, Zeta potential ranged (from -16.955±7.372 to -23.22±0.880) mV and with entrapment efficiency % ranged (from 57.30±6.48% to 77.77±3.78%). The best formula F5 showed vesicle size (160.60±15.82) nm, Zeta potential (-20.75±0.930) mV, and entrapment efficiency %(77.77±3.78%) with 84.39% in-vitro release of RH after 24 h. It is concluded that bilosomes are good nanovesicular carriers for enhancing oral drug delivery and providing the sustained release of RH and all that may enhance oral bioavailability for RH.